Liquid Gold for Life: Exploring Mothers’ Perspectives on Human Milk Donation and Banking - Bahl, Heena; Sheoran, Poonam; Kaur, Simarjeet; Sarin, Jyoti (Journal of Neonatal Surgery, 2025)
Background: Neonatal mortality remains a major public health concern globally, with India bearing a disproportionately high burden. Breastfeeding is a critical strategy to improve neonatal survival, yet when a mother’s milk is unavailable, donor human milk can serve as an optimal alternative. Despite its proven benefits, limited awareness and cultural reservations often impede the acceptance of human milk donation and banking. Objectives: This study aimed to (1) assess mothers’ knowledge and attitudes toward human milk donation and banking; (2) explore the sociocultural, religious, and familial factors influencing their willingness to donate; and (3) identify perceived barriers and facilitators to establishing human milk banks in a semi-urban and rural context. Methods: A descriptive, cross-sectional survey was conducted among 370 postnatal mothers (0–6 months postpartum) residing in rural and urban areas of Ambala, Haryana. Data were collected through a structured opinionnaire, covering socio-demographics, maternal and infant profiles, breastfeeding practices, and detailed items on human milk donation/banking. Descriptive statistics were used to quantify responses, and chi-square tests examined associations between willingness to donate and key variables (p < 0.05). Results: Although only 4.32% of participants had heard of human milk donation and 2.43% knew of human milk banking, the majority (78.11%) expressed a willingness to donate if they had excess milk. Nearly all (99.46%) believed society needs human milk banks, underscoring strong latent acceptance. Religious barriers, lack of family support, and fear of insufficient milk were the main deterrents. Urban residence, nuclear family type, and absence of pregnancy complications were positively associated with willingness to donate. Conclusion: Despite limited prior awareness, mothers demonstrated high receptivity to human milk donation and banking once informed. Targeted education, culturally sensitive outreach, and supportive healthcare policies could significantly enhance community acceptance and optimize the lifesaving potential of donor human milk.